Competition vs. Stability : Oligopolistic Banking System with Run Risk - Capelle, Damien (IMF Working Papers; Working Paper, 2021)
This paper develops a model where large financial intermediaries subject to systemic runs internalize the effect of their leverage on aggregate risk, returns and asset prices. Near the steady-state, they restrict leverage to avoid the risk of a run which gives rise to an accelerator effect. For large adverse shocks, the system enters a zone with high leverage and possibly runs. The length of time the system remains in this zone depends on the degree of concentration through a franchise value, price-drop and recapitalization channels. The speed of entry of new banks after a collapse has a stabilizing effect.